Lineamientos metodológicos para evaluar el impacto de proyectos de perforación exploratoria de petróleo crudo sobre la calidad del aire (2020)
A methodology is proposed; it consisted of gathering the existing data, characterizing the emission sources with it and, finding the background concentration. Thereafter, an inventory of emissions which served to perform a pollutants dispersion modeling was made. The results were compared to the maximum limits permitted by the regulations and, then concentration isopleths were charted to delimit geographically the area in which the permitted limits were exceeded, that is to say, the area of influence. To formulate the methodology, a literature review regarding Environmental impact assessment aspects was carried out: (Adelle & Weiland, 2012) (Calderón, Martínez Prad, & Arrieta Loyo, 2013) (Kozová, Drdoš , Pavličková, & Úradníček, 1996) (Morgan, 2012) (Retief, 2010); and, regarding the atmospheric component: (García Leyton, 2004) (IDEAM, 2002) (Khaniabadi, y otros, 2018) (Kumar, Mulheron, Fisher, & Harrison, 2012) (Kumar, Mulheron, & Som, 2012). To identify the relevant features in the assessment of impacts on the hydrocarbons sector, a detailed analysis of Environmental impact studies, approved by the National Environmental Licensing Agency (in its Spanish acronym), of three exploratory drilling projects in Colombia that were granted the Environmental License, was done. All this to know the impact assessment process in the air component that is currently being implemented in Colombia. The air quality regulation (Ministerio de Ambiente y Desarrollo Sostenible, 2017) and, the published reference terms by the ANLA (ANLA 2010) were consulted. The literature review findings suggest that pollutant dispersion modeling is a fundamental technological tool to delimit the AID (in its Spanish acronym) of the air component. For this reason, it was necessary to create a methodology that can be useful to include the models within the EIA (in its Spanish acronym).